3D tomographic analysis of equatorial plasma bubble using GNSS-TEC data from Indonesian GNSS Network - Ihsan Naufal Muafiry; Prayitno Abadi; Teguh N. Pratama; Dyah R. Martiningrum; Sri Ekawati; Yuandhika G. Wismaya; Febrylian F. Chabibi; Gatot H. Pramono (Earth and Planetary Physics)
Equatorial Plasma Bubbles (EPBs) are ionospheric irregularities that take place near the magnetic equator. EPBs most commonly occur after sunset during the equinox months, although they can also be observed during other seasons. The phenomenon significantly disrupts radio wave signals essential to communication and navigation systems. The national network of Global Navigation Satellite System (GNSS) receivers in Indonesia (>30° longitudinal range) provides an opportunity for detailed EPB studies. To explore this, we conducted preliminary 3D tomography of total electron content (TEC) data captured by GNSS receivers following a geomagnetic storm on December 3, 2023, when at least four EPB clusters occurred in the Southeast Asian sector. TEC and extracted TEC depletion with a 120-minute running average were then used as inputs for a 3D tomography program. Their 2D spatial distribution consistently captured the four EPB clusters over time. These tomography results were validated through a classical checkerboard test and comparisons with other ionospheric data sources, such as the Global Ionospheric Map (GIM) and International Reference Ionosphere (IRI) profile. Validation of the results demonstrates the capability of the Indonesian GNSS network to measure peak ionospheric density. These findings highlight the potential for future three-dimensional research of plasma bubbles in low-latitude regions using existing GNSS networks, with extensive longitudinal coverage.